2019
DOI: 10.1186/s12906-019-2755-6
|View full text |Cite
|
Sign up to set email alerts
|

Water-separated part of Chloranthus serratus alleviates lipopolysaccharide- induced RAW264.7 cell injury mainly by regulating the MAPK and Nrf2/HO-1 inflammatory pathways

Abstract: BackgroundChloranthus serratus (Chloranthaceae) has been used to treat bruises, rheumatoid and bone pain. However, the anti-inflammatory mechanisms of C. serratus in vitro have not been fully elucidated. The present study aimed to explore the anti-inflammatory activity and potential mechanisms of C. serratus’s separated part of water (CSSPW) in lipopolysaccharide (LPS)-induced RAW264.7 cells.MethodsThe concentrations of CSSPW were optimized by CCK-8 method. Nitric oxide (NO) content was detected by one-step me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The sample solution was obtained by dissolving 0.05 g of chloroform separation site (CF), ethyl acetate separation site (EA), n-butanol separation site (NB) and water separation site (WA) with 75% ethanol to a concentration of 1 mg/ml. After blank correction of a Ultrospec 7000 spectrophotometer (Biochrom, Ltd.) with 75% ethanol, the solutions were scanned under the following spectral conditions: Data mode, absorbance; scanning range, 190-500 nm; scanning speed, medium; step, 1.0 nm; bandwidth, 2.0 nm; lamp mode, pulse ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample solution was obtained by dissolving 0.05 g of chloroform separation site (CF), ethyl acetate separation site (EA), n-butanol separation site (NB) and water separation site (WA) with 75% ethanol to a concentration of 1 mg/ml. After blank correction of a Ultrospec 7000 spectrophotometer (Biochrom, Ltd.) with 75% ethanol, the solutions were scanned under the following spectral conditions: Data mode, absorbance; scanning range, 190-500 nm; scanning speed, medium; step, 1.0 nm; bandwidth, 2.0 nm; lamp mode, pulse ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…C. serratus is rich in terpenoids (such as chlorophenyl lactone C, acetaminone and shizukanolide C, E and F) and it has good anti-inflammatory effects in the clinic ( 10 ). Our previous study demonstrated that the water-separated site of C. serratus exerts anti-inflammatory activity in a dose-dependent manner in LPS-induced RAW264.7 cells ( 11 ). Studies on C. serratus worldwide have mainly been limited to species identification and chemical composition analysis ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sample solutions were obtained by dissolving 0.05 g of the ER, ES and EL in 75% ethanol to obtain a concentration of 1 mg/mL, respectively. After blank correction with 75% ethanol, the solutions were scanned by using a Hitachi U-5100 spectrophotometer (Hitachi High-Tech Science Corporation, Japan) under the following spectral conditions: data mode: Abs; scanning range: 190-500 nm; scanning speed: 400 nm/min; delay: 0 s; response: fast; sampling interval: 1.0 nm; cycle time: 1.0 min; and slit width: 5.0 nm (Sun et al 2019).…”
Section: Plant Materials Extract Preparation and Uv Fingerprint Analysismentioning
confidence: 99%
“…Previous experiments have shown that the ethanol extract of C. serratus roots has obvious anti-inflammatory activity (Sun and Li 2013). Moreover, the water-extractable components of C. serratus might exert an antiinflammatory effect by inhibiting pro-inflammatory cytokines and mediators in lipopolysaccharide-stimulated macrophages (Sun et al 2019). The evaluation of the therapeutic effect on arthritis in vivo has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Chinese Medicine Dictionary (NUTCM 2006), C. serratus has many therapeutic effects, including dispelling wind, relieving pain, promoting blood circulation to dissipate blood stasis, and treating injuries from fall, rheumatic pain, and other symptoms. Moreover, the water-extractable components of C. serratus might exert an anti-inflammatory effect in lipopolysaccharide-stimulated macrophages (Sun et al 2019b), and the anti-arthritic activity of different parts of C. serratus in adjuvant arthritis rats is related to inhibiting the release of inflammatory cytokines and improving antioxidant capacity (Sun et al 2020b).…”
Section: Introductionmentioning
confidence: 99%